TRANSITION FROM PRONE TO SUPINE PERCUTANEOUS NEPHROLITOTOMY: EVALUATING THE LEARNING CURVE FROM THE SINGLE SURGEON EXPERIENCE - Ali, Zulfikar; Afriansyah, Andika (Indonesian Journal of Urology, 2021)
Objective: This study aims to evaluate the learning curve of the urologist to perform supine PCNL and the perioperative outcome of patients based on a single surgeon’s experience. Material & Methods: 60 consecutive patients who underwent modified supine PCNL for renal stone were analyzed. A single experienced urological surgeon performed the supine PCNL. Mean operative time, drop in hemoglobin level, stone-free rate, complications, and length of hospital stay were analyzed to evaluate the learning curve of the surgeon. All parameters were compared among all six groups obtained from the 60 cases in chronological order. Besides, the outcomes of supine PCNL were also compared to prone PCNL. Results: Mean operative time from 60 cases of supine PCNL was 100 ± 27 minutes. The mean operative time was decreased over time, particularly after 20 cases. Significantly different mean operative times (89 ± 14 minutes vs. 126 ± 21 minutes, p < 0.001) in the groups of cases 21-60 compared to the group of 1–20 cases were observed. The total stone-free rate for supine PCNL from all cases was 68%. There was no difference regarding the reduction of hemoglobin level, stone-free rate, hospital stay, and complication rate. No major complication was found among study subjects. Supine PCNL showed similar outcome parameters compared to prone PCNL. Conclusion: The surgeon acquired the surgical competencies to perform supine PCNL after 20 cases. The supine PCNL could remove the kidney stone as effective and safe as prone PCNL.